FAKTOR YANG BERHUBUNGAN DENGAN KEPATUHAN IBU HAMIL MENGKONSUMSI TABLET FE - Ainal Mardiah; Widya Nengsih; Indreswati Indreswati; Rezky Agusnur Rizita (STIKes Al-Insyirah Pekanbaru, 2022)
The low percentage of pregnant women who received Fe tablets at the Rambatan II Community Health Center in 2020 was 34.7% and there was still an anemia rate in pregnant women in 2022 in the working area of ​​that Community Health Center. The purpose of this study was to determine the factors related to the obedience of pregnant women in consuming Fe tablets in the working area of Rambatan II Community Health Center Tanah Datar Regency. The research method was analytic with cross sectional design. The results showed that 48.1% of respondents were knowledgeable enough, 66.7% had negative attitudes and 83.3% husbands were supportive. The results of the analysis of each variable with chi square stated that there was a significant correlation between knowledge of pregnant women and adherence to consuming Fe tablets (p value = 0.003), then there was a significant correlation between attitudes of pregnant women and adherence to consuming Fe tablets (p value = 0.026), and there was no significant correlation between husband's support and adherence to consuming Fe tablets (p value = 0.065). It was concluded that there was a significant correlation between knowledge and attitude with the adherence of pregnant women to consume Fe tablets and there was no significantcorrelation between husband's support and adherence to consuming Fe tablets. Health workers are advised to provide and improve information about the benefits of Fe tablets so that people are motivated to comply with consuming these Fe tablets.